THE ATTITUDE OF THE LANGUAGE OF UZBEK FILMS AT THE PERIOD OF INDEPENDENCE TO THE LEXICAL NORMS - Shirinova, Mexrigiyo (FILOLOGIYA UFQLARI JURNALI, 2024)
The language of the Uzbek films of the period of independence is considered to be an appearance of oral speech, and the lexical meaning plays an important role in it. When generating lexical meaning in the language of cinema, it is necessary to take into account the lexical norm. The article analyzes the language of Uzbek films shot in the period of independence, selected as a source and their attitude to lexical norms. The following lexical errors are listed in the films: 1) ignorance of the lexical meaning of the word, 2) violation of the lexical consistency of words, 3) logical distortion of speech, 4) violation of chronological sequence, 5) irregularity in the use of euphemisms (softening of rough meaning), 6) composing phrases without taking into account the stylistic dye, 7) allowing redundancy in speech, 8) inconsistency in the use of words such as synonyms, paronyms. Each lexical error is explained with examples and the correct variant of these errors is mentioned as a recommendation.